HFE Mutations in Caucasian Participants of the Hemochromatosis and Iron Overload Screening Study with Serum Ferritin Level <1000 μg/L - Paul C Adams; Christine E McLaren; Mark Speechley; Gordon D McLaren; James C Barton; John H Eckfeldt (Canadian Journal of Gastroenterology)
BACKGROUND: Many patients referred for an elevated serum ferritin level <1000 μg/L are advised that they likely have iron overload and hemochromatosis.